Associations between childhood maltreatment and risk of myocardial infarction in adulthood: Results from the National Epidemiologic Survey on alcohol and Related Conditions. (September 2019) - Chou, Po-Han; Koenen, Karestan C.
Abstract: Objective: Although childhood maltreatment has been reported to be associated with the incidence of cardiovascular diseases, its association with specific major cardiovascular events remains unclear. This study aimed to examine the relationship between different types of childhood maltreatment (CM) and myocardial infarction (MI) occurrence in a nationally representative sample. Methods: We used data from the National Epidemiologic Survey of Alcohol and Related Conditions, a nationally representative US sample of adults aged 20 years and older (N = 34, 653). Logistic regression models were constructed to investigate the associations between five types of CMs including physical abuse, physical neglect, emotional abuse, emotional neglect, and sexual abuse and the risk of MI adjusting for sociodemographic variables. Results: After adjusting for sociodemographic variables, childhood sexual abuse was significantly associated with increased odds of MI occurrence (adjusted odds ratio [aOR] = 1.85, 95%CI = 1.24–2.76, p = 0.003). Additionally, childhood physical abuse was significantly associated with increased odds of MI occurrence in men (aOR = 2.45, 95%CI = 1.35–4.44, p = 0.004) but this association was not observed in women (aOR = 0.72, 95%CI = 0.32–1.66, p = 0.440). Compared to those who did not experience CM, those who experienced more than three types of CMs showed increased odds of MI occurrence (adjusted OR = 2.08–3.05, all p < 0.05). Conclusions: Using data from a nationally representative US sample of adults, we found significant positive associations between CM and odds of MI occurrence in adulthood. Future longitudinal prospective studies are needed to confirm our findings. Highlights: This study investigated the association between childhood maltreatment and risk of myocardial infarction in adulthood. Sexual abuse was significantly associated with odds of MI occurrence and physical abuse was significantly associated with increased odds of MI occurrence in men. Those who suffered more than three types of maltreatment showed increased odds of MI. Early interventions are warranted to prevent long-term physical sequelae in those who suffer from childhood maltreatment.